Identification of potential plasma markers for hepatitis B virus‐related chronic hepatitis and liver fibrosis/cirrhosis. Issue 8 (14th April 2022) - Zhao, Dandan; Yu, Songhao; Guo, Peilin; Zhang, Xiaoxiao; Tang, Yuhui; Dong, Chen; Zhao, Suxian; Li, Lu; Al‐Dhamin, Zaid; Ai, Rong; Xue, Ningning; Dong, Shiming; et al.
Abstract: The aim of this study was to identify potential plasma biomarkers for hepatitis B virus (HBV)‐related liver diseases. High‐throughput transcriptome sequencing analysis was performed on five patients with chronic hepatitis B (CHB), five patients with HBV‐associated liver fibrosis/liver cirrhosis (LF/LC), and four healthy participants. By short time‐series expression miner and functional analysis, aquaporin 1 (AQP1), dystroglycan 1 (DAG1), and hemoglobin subunit beta (HBB) were identified as potential biomarkers. Immunohistochemical analysis revealed that the expression levels of AQP1, DAG1, and HBB were upregulated in the three groups. Subsequent enzyme‐linked immunosorbent assay tests on the training cohort ( n  = 150) indicated that the plasma levels of AQP1 and DAG1 were highest in LF/LC patients, followed by those in CHB patients, and the lowest in healthy controls. APAD model, a diagnostic panel incorporating age, platelet, AQP1, and DAG1 levels, exhibited the strongest stratification ability to distinguish LF/LC patients from CHB patients, and to differentiate CHB patients from healthy controls. Furthermore, the diagnostic accuracies of the biomarkers and APAD model were verified in an independent cohort consisting of 230 participants. In conclusion, both AQP1 and DAG1 have good diagnostic values and APAD model greatly enhances the diagnostic accuracy for HBV‐related hepatic diseases.